MAJOR TRENDS IN THE 20TH CENTURY LANGUAGE TEACHING (Web of Teachers: Inderscience Research, 2026)
The 20th century witnessed significant transformations in the field of English language teaching (ELT), shaped by evolving pedagogical theories, technological advancements, and sociocultural changes. This abstract explores the major trends that emerged during this period, highlighting key methodologies and approaches that influenced language instruction. Overall, the 20th century marked a dynamic evolution in English language teaching, characterized by a shift from teacher-centered approaches to learner-centered methodologies. These trends reflect broader educational philosophies and societal changes, setting the stage for contemporary practices in ELT that continue to evolve in response to globalization and digitalization.